The anxiety of sameness in early modern Spain - Lee, Christina H., 1973- (Book collections on Project MUSE., 2016)
"This book explores the Spanish elite's fixation on social and racial 'passing' and 'passers', as represented in a wide range of texts. It examines literary and non-literary works produced in the sixteenth and seventeenth centuries that express the dominant Spaniards' anxiety that socially mobile lowborns, Conversos (converted Jews), and Moriscos (converted Muslims) could impersonate and pass for 'pure' Christians like themselves. Ultimately, this book argues that while conspicuous sociocultural and ethnic difference was certainly perturbing and unsettling, in some ways it was not as threatening to the dominant Spanish identity as the potential discovery of the arbitrariness that separated them from the undesirables of society - and therefore the recognition of fundamental sameness."--